Psychological Cost, Religiusitas, Love of Money dan Kepatuhan Wajib Pajak Badan Sektor UMKM - Artharini, Ni Kadek Rahayu; Noviari, Naniek (E-Jurnal Akuntansi; Vol 31 No 5 (2021)DO - 10.24843/EJA.2021.v31.i05.p20, 2020)
MSMEs play a very important role in encouraging the acceleration of a country's economic growth. This study aims to determine the effect of psychological cost, religiosity, and love of money on the taxpayer compliance of the MSMEs sector registered in the East Denpasar Tax Office. Incidental sampling is used as a method of determining the sample and obtained a sample of 96 MSMEs. The data analysis technique used is multiple linear regression analysis techniques. The results showed that psychological cost and religiosity had a positive effect on the compliance of the Taxpayers of the MSME sector, while love of money had a negative effect on the compliance of the Taxpayers of the MSMEs sector. Keywords: Psychological Cost; Religiosity; Love of Money; Corporate Compliance Tax Payer’s.